Edge/cloud task offloading for time-sensitive applications: a hybrid approach with ant colony optimization and simulated annealing - Ramasubramanian, Shreya (Nanyang Technological University, 2023)
With the proliferation of Internet of Things (IoT) devices, the volume of big data generated and the number of IoT-powered applications have surged. Processing this data with low latency and minimal data transport costs while upholding Quality of Service (QoS) standards has become imperative. Fog computing has emerged as a solution, introducing computational nodes at the edge of the network to reduce reliance on the centralized cloud. While fog computing enhances performance, it also introduces complexity by adding limited, dynamic, and heterogeneous resources to the network.